How the World Council of Churches is ending with ecumenism - Hille, Rolf (Vox Scripturae - Revista Teológica Internacional, 2014)
The present article presents a brief history of the emergence of the World Council of Churches – WCC, and, above all, it concentrates in presenting some of its contemporary tendencies, based on the preparatory text for the 10th General Assembly, held in 2013 and Busan, South Korea, entitled:Together Towards Life: Mission and Evangelism in Changing Landscapes. The author, Director of Ecumenical Affairs of the World Evangelical Alliance, presents a series of questions on the WCC text. It criticizes, specially, the unilateral comprehension of mission from the first article, of creation, as well as thesuppression of the announcement of Jesus Christ as the one who saves from sin. It criticizes, still, the reductionism in the comprehension of evil, while it is unilaterally associated to the neoliberal political and economic structures of the market. At the end, the author emphasizes that the new tendencies of the WCC represent an abandonment of the common ecumenical fundament and represent a regression in the ecumenical dialogue.
Keywords: World Council of Churches; ecumenism; World Evangelical Alliance; mission and evangelization.